Vitamin D deficiency and risk of recurrent aphthous stomatitis: updated meta-analysis with trial sequential analysis - Al-Maweri, Sadeq Ali; Al-Qadhi, Gamilah; Halboub, Esam; Alaizari, Nader; Almeslet, Asma; Ali, Kamran; Osman, Safa A. Azim (Frontiers in Nutrition, 2023)
Background Growing evidence suggests a significant association between vitamin D deficiency and RAS. Hence, the present meta-analysis and trial sequential analysis sought to investigate the potential association between low serum vitamin D levels and RAS. Methods PubMed, Scopus, Embase, and Web of Science were comprehensively searched on December 1st, 2022 to retrieve all relevant studies. The grey literature was also searched via ProQuest. All case-control studies on the association between vitamin D and RAS were considered. The quality appraisal of the included studies was done using Newcastle-Ottawa scale. RevMan 5.0 and trial sequential analysis (TSA) programs were used for analyses. Results A total of 14 case-control studies with 1468 subjects (721 RAS patients and 747 controls) were included. The pooled data revealed a significant association between low serum levels of vitamin D and the risk of RAS (mean difference = – 8.73, 95% CI: – 12.02 to – 5.44, I2 = 94%, P < 0.00001). Additionally, TSA findings indicated that the current studies surpassed the required information size, confirming that the differences were reliable. Conclusion The available evidence suggests that Vitamin D deficiency may have a role in the pathogenesis of RAS. Therefore, evaluation of vitamin D should be considered in RAS patients. Additionally, the results support the possibility of using vitamin D supplements in the management of RAS patients with inadequate serum levels of vitamin D. Future interventional studies are required to evaluate the benefits of vitamin D replacement in prevention and treatment of RAS.